2004
DOI: 10.1128/iai.72.9.5247-5252.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Lectin Pathway of Complement Activation in Antimicrobial Immune Defense during Experimental Septic Peritonitis

Abstract: A critical first line of defense against infection is constituted by the binding of natural antibodies to microbial surfaces, activating the complement system via the classical complement activation pathway. In this function, the classical activation pathway is supported and amplified by two antibody-independent complement activation routes, i.e., the lectin pathway and the alternative pathway. We studied the contribution of the different complement activation pathways in the host defense against experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
2
19
0
2
Order By: Relevance
“…In a non-severe model of polymicrobial peritonitis, mice deficient in C1q (lack classical pathway) or deficient in cfB and C2 (lack all three pathways) have an increased mortality rate compared to WT mice, indicating a critical contribution of the three complement pathways to host defense (56). However, under severe septic and hyper-inflammatory conditions, they may be improperly controlled and may contribute to tissue injury and organ failure (57).…”
Section: Discussionmentioning
confidence: 99%
“…In a non-severe model of polymicrobial peritonitis, mice deficient in C1q (lack classical pathway) or deficient in cfB and C2 (lack all three pathways) have an increased mortality rate compared to WT mice, indicating a critical contribution of the three complement pathways to host defense (56). However, under severe septic and hyper-inflammatory conditions, they may be improperly controlled and may contribute to tissue injury and organ failure (57).…”
Section: Discussionmentioning
confidence: 99%
“…These are generated after activation of the alternative pathway of complement via deposition of C3b to target surfaces by so-called spontaneous tickover of fluid phase C3 or by activation of classical or lectin pathways (via recognition of immune complexes or carbohydrate moieties on microorganisms, respectively). C1q-deficient mice (deficient of the recognition molecule of the classical pathway) and mice with a dual deficiency of factor B and C2 (affecting activities for lectin, classical and alternative pathways) (all on Sv/129 background) have previously been studied in sublethal CLP (12). The study concluded that intact lectin and alternative pathways are important for survival of sublethal CLP; however, it did not allow quantification of the separate contribution of the alternative pathway amplification to this effect.…”
Section: Ecal Ligation and Puncture (Clp)mentioning
confidence: 99%
“…A later study found that serum MBL-A and MBL-C levels were reduced for 1 week after CLP, while the mRNA levels where unchanged, indicating consumption rather than decreased protein expression 41 . Another study found that ficolin-B mRNA expression was higher in neutrophils isolated from mice subjected to CLP compared to naive mice 42 .…”
Section: Discussionmentioning
confidence: 94%